INTEGRATIVE TAXONOMY AND FISHING SEASON OF SCOMBRINI-SARDINI (FAMILY: SOMBRIDAE) FISHERY CAUGHT AROUND LAMONGAN, EAST JAVA - Wiadnya, Dewa Gede Raka; Anam, M Choirul; Yulianto, Eko Sulkhani; Paricahya, Akhsan Fikrillah; Hariati, Anik Martinah (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2025)
The world finfish database reports that Indonesia has more than 3,647 species of marine fish in the finfish category. Fisheries statistical data divides marine fishery catches into 92 species categories. It is very possible for one species category to be composed of more than 15 different taxonomic species. This research aims to analyze the composition of kembung-mackerel species as representatives of the small pelagic group, including the composition of catches in the Purse Seine and the peak fishing season. A total of 15 specimens in the mackerel fish category were sampled to trace morphological and genetic characters (COI region DNA analysis). Other fish were also searched for local names and morphological characters. A total of 744 Purse Seine catch data were monitored from three TPIs in Lamongan: Kranji, Labuhan, and Lohgung between February to July 2023. At the same time, monthly data compilations were also collected from January 2018 to May 2023. The results of DNA analysis found four identified species often reported as mackerel fish, are: Rastrelliger brachysoma, R. faughni, Scomber australasicus, and Sarda orientalis. These results are in accordance with the morphological characters of the keel (caudal peduncle), inter-dorsal region (between the first and second fins), finlets, and combination of ornaments in the dorsal and ventral regions. All these characteristics make it different from other members within the Scombrid family. Mackerel as a whole constitutes 37.1±24.2% of the total catch after tongkol (little-tuna). The peak mackerel fishing season starts from April to July, preceding the peak tongkol fishing season which starts from October to February the following year. Knowledge about this season is often used as a basis by fishermen to change the size of fishing gear, in adaptation to environmental conditions.